PENYULUHAN MENGENAI PERILAKU SADARI DALAM UPAYA MENGATASI KANKER PAYUDARA PADA SISWA SMA NEGERI II KOTABUMI LAMPUNG UTARA - Satria Nandar Baharza; Dian Utama Pratiwi Putri (Universitas Malahayati Lampung, 2019)
ABSTRACT : SERVICE QUALITY PERCEPTIONS AND PATIENT SATISFACTION: A STUDY OF PUBLIC HEALTH CENTRES AT WAY HALIM BANDAR LAMPUNG 2018 Background : Patients’ perceptions about health services seem to have been largely ignored by health care providers in developing countries. That such perceptions, especially about service quality, might shape confidence and subsequent behaviors with regard to choice and usage of the available health care facilities is reflected in the fact that many patients avoid the system or avail it only as a measure of last resort. Public services are the responsibility of the government and implemented by government The pre-survey of Public Health Centres (Puskesmas) service satisfaction in Bandar Lampung is still under the standard, whereas the satisfaction index of respondents to service at Public Health Centers (Puskesmas) at Way Halim 71, 66%.Purpose: the relationship of service quality to outpatient satisfaction level at Way Halim Health Center Bandar Lampung City 2018.Methods : This research is a quantitative research, using Analytical Survey method with Cross Sectional approach. The research was conducted is approved at Way Halim Public Health Center of Bandar Lampung City in February 2018. The population in this study is the average number of patients per month 435 people, sample 207 people. Sampling technique with accidental sampling. Data collection using questionnaire sheet. Data processing editing, coding, processing, cleaning. Analysis of data with univariate and bivariate (Chi Square).Results : Known as 126 (60,9%) said satisfied, 102 (49,3%) medical support facillities, 96 (46,4%) good reliability, 105 (50,7%) good responsiveness, 126 60.9%) good guarantees and as many as 51 (24.6%) good empathy.Conclusion : There is a correlation between physical evidence (p-value: 0,000 and OR: 3,859), reliability (p-value: 0,000 and OR: 4,202), responsiveness (p-value: 0,000 and OR: 4,725), assurance (p-value: 0.000 and OR: 5,440) and empathy (p-value: 0,000 and OR: 6,944) with patient satisfaction of Puskesmas Way Halim Bandar Lampung City. It is expected to further improve the development effort in patient service, such as: clear to the family, provide motivation to the officers such as giving exemplary staff rewards.Keywords: Quality of service, satisfaction, public health centres, outpatient Pendahuluan : Persepsi pasien tentang layanan kesehatan tampaknya telah diabaikan oleh penyedia layanan kesehatan di negara-negara berkembang. Bahwa persepsi seperti itu, terutama tentang kualitas layanan, dapat membentuk kepercayaan diri dan perilaku selanjutnya sehubungan dengan pilihan dan penggunaan fasilitas perawatan kesehatan yang ada tercermin dalam kenyataan bahwa banyak pasien menghindari sistem atau memanfaatkannya hanya sebagai upaya terakhir. Survei kepuasan layanan Puskesmas di Kota Bandar Lampung masih di bawah standar, sedangkan indeks kepuasan responden untuk pelayanan di Puskesmas Way Halim 71, 66%.Tujuan : diketahui hubungan kualitas pelayanan dengan tingkat kepuasan pasien rawat jalan di Puskesmas Way Halim Kota Bandar Lampung 2018. Metode : Penelitian ini merupakan penelitian kuantitatif, dengan menggunakan metode Analytical Survey dengan pendekatan Cross Sectional. Penelitian telah dilakukan di Puskesmas Way Halim Kota Bandar Lampung pada bulan Februari tahun 2018. Populasi dalam penelitian ini adalah rata-rata jumlah pasien per bulan sebanyak 435 orang, sampel 207 orang. Teknik sampling dengan accidental sampling. Pengumpulan data menggunakan lembar kuesioner. Pengolahan data editing, coding, processing, cleaning. Analisis data dengan univariat dan bivariat (Chi Square).Hasil : Diketahui sebanyak 126 (60,9%) mengatakan puas, sebanyak 102 (49,3%) bukti fisik baik, sebanyak 96 (46,4%) kehandalan baik, sebanyak 105 (50,7%) daya tanggap baik, sebanyak 126 (60,9%) jaminan baik dan sebanyak 51 (24,6%) empati baik.Kesimpulan : Ada hubungan antara bukti fisik (p-value: 0,000 dan OR: 3,859), kehandalan (p-value: 0,000 dan OR: 4,202), daya tanggap (p-value: 0,000 dan OR: 4,725), jaminan (p-value: 0,000 dan OR: 5,440) dan empati (p-value: 0,000 dan OR: 6,944) dengan kepuasan pasien Puskesmas Way Halim Kota Bandar Lampung tahun 2018. Diharapkan lebih meningkatkan upaya pengembangan dalam pelayanan pasien, seperti: membuat suatu prosedur penerimaan pasien yang singkat dan jelas kepada pihak keluarga, memberikan motivasi ke petugas seperti pemberian reward pegawai teladan. Kata kunci : Mutu Pelayanan, Kepuasan, Rawat Jalan